2011
DOI: 10.1093/jxb/err314
|View full text |Cite
|
Sign up to set email alerts
|

Induction of root Fe(lll) reductase activity and proton extrusion by iron deficiency is mediated by auxin-based systemic signalling in Malus xiaojinensis

Abstract: Iron is a critical cofactor for a number of metalloenzymes involved in respiration and photosynthesis, but plants often suffer from iron deficiency due to limited supplies of soluble iron in the soil. Iron deficiency induces a series of adaptive responses in various plant species, but the mechanisms by which they are triggered remain largely unknown. Using pH imaging and hormone localization techniques, it has been demonstrated here that root Fe(III) reductase activity and proton extrusion upon iron deficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 36 publications
(53 reference statements)
7
58
0
1
Order By: Relevance
“…In addition to ethylene, other hormones and signaling substances, such as auxin and nitric oxide (NO), have been involved in the up-regulation of Fe and P acquisition genes [3,4,29,68,[75][76][77][78][79][80][81]. In both deficiencies, the activating effect of auxin, ethylene and NO depend on the Fe or P status of the plants [68,69,75,76], which suggests the existence of additional Fe-and P-related signals acting in conjunction with ethylene, auxin and NO [82].…”
Section: Hormones and Signaling Substances In The Regulation Of Fe Anmentioning
confidence: 99%
“…In addition to ethylene, other hormones and signaling substances, such as auxin and nitric oxide (NO), have been involved in the up-regulation of Fe and P acquisition genes [3,4,29,68,[75][76][77][78][79][80][81]. In both deficiencies, the activating effect of auxin, ethylene and NO depend on the Fe or P status of the plants [68,69,75,76], which suggests the existence of additional Fe-and P-related signals acting in conjunction with ethylene, auxin and NO [82].…”
Section: Hormones and Signaling Substances In The Regulation Of Fe Anmentioning
confidence: 99%
“…Since previous studies have shown that auxins play a critical role in the regulation of Fe deficiency responses (Chen et al, 2010b;Jin et al, 2011;Wu et al, 2012b), it is therefore necessary to clarify whether auxins have an association with Suc in the regulation of Fe deficiency responses. As shown in Figure 9, in the presence of the auxin transport inhibitor NPA, the stimulating effect of Suc on root FCR activity and expression of IRT1, FRO2, and FIT in Fedeficient Col-0 plants were completely terminated.…”
Section: Suc-modulated Fe Deficiency Responses Depend On the Auxin Simentioning
confidence: 99%
“…In addition to the above transcription factors, we and others showed that the chemical molecules, auxins and nitric oxide (NO), both of which accumulate to higher levels in Fe-deficient plants, are also two general regulators controlling the initiation of adaptations to Fe deficiency in Strategy I plants (Graziano and Lamattina, 2007;Jin et al, 2009Jin et al, , 2011Chen et al, 2010b;Bacaicoa et al, 2011;Wu et al, 2012b). The NO acts upstream of FIT to trigger Fe deficiency responses through a mechanism of reducing the proteasomal degradation of FIT (Meiser et al, 2011), while the elevation of auxin levels is required for the regulation of increased synthesis of NO under Fe-deficient conditions (Chen et al, 2010b;Jin et al, 2011).…”
mentioning
confidence: 99%
“…Fe-deficiency induced an obvious increase of IAA level in the branch apex and treatments of IAA to the branch apex induced Fe deficiency responses in M. xiaojinensis (Wu et al 2012). In the present study, the expression levels of MdNAS1 were affected by IAA and ABA treatments in the leaf, and phloem of M. domestica seedlings.…”
Section: Discussionmentioning
confidence: 95%
“…The expression of MxNAS1 and MxNAS2 in M. xiaojinensis was also affected by IAA and ABA treatments and the expression levels in root and mature leaf of M. xiaojinensis all increased (Han et al 2013. Fe-deficiency also induced a level increase of IAA in the shoot apex of M. xiaojinensis and treatments of IAA to the shoot apex induced Fe deficiency responses (Wu et al 2012).…”
Section: Introductionmentioning
confidence: 96%